Corporate governance innovation framework to reduce credit risk in MSMEs using blockchain technology - Mutamimah Mutamimah; Suryani Alifah; Made Dwi Adnjani (Cogent Business & Management, 2023)
This study aims to design a framework of corporate governance innovation to reduce the credit risks of Micro, Small and Medium Enterprises (MSMEs) by using blockchain technology. The research design uses a qualitative approach with Grounded theory analysis for data analysis with open, axial, and selective coding. This framework consists of two stages, namely development and validation. In-depth interviews are used for data collection to develop the framework while focus group discussions are used for validation. The in-depth interviews are carried out with various stakeholders, such as the government, association, MSMEs, suppliers, and banking. Findings show that blockchain technology as corporate governance innovation framework has the potential to reduce asymmetric information and credit risk. The reason is that blockchain technology can facilitate recording, immutable, partial decentralisation, and storage of business and financial transactions on a digital network and all stakeholders can access information in a transparent and valid manner that can increase transparency, accountability, responsibility, and fairness. Results of the focus group discussion indicate the validity of the proposed framework.
Keywords: 650; blockchain technology; corporate governance innovation; credit risk